2014
DOI: 10.1016/j.celrep.2014.11.030
|View full text |Cite
|
Sign up to set email alerts
|

ELAVL1 Modulates Transcriptome-wide miRNA Binding in Murine Macrophages

Abstract: SUMMARY Post-transcriptional gene regulation by miRNAs and RNA binding proteins (RBP) is important in development, physiology and disease. To examine the interplay between miRNAs and the RBP ELAVL1 (a.k.a. HuR), we mapped miRNA binding sites at the transcriptome-wide scale in WT and Elavl1 knockout murine bone marrow-derived macrophages. Proximity of ELAVL1 binding sites attenuated miRNA binding to transcripts and promoted gene expression. Transcripts that regulate angiogenesis and macrophage/endothelial cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 56 publications
0
55
0
2
Order By: Relevance
“…HuR can also interact with several noncoding (nc)RNAs. It was found to associate with the microRNA let-7, 6,7 although the consequences of this interaction are unclear, and with several long noncoding (lnc)RNAs, including LINCRNAP21, HOTAIR, and RMRP, influencing their stability or subcellular localization. 6,8,9 However, whether or not HuR binds to circular RNAs (circRNAs) and the functional consequences of these interactions have not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…HuR can also interact with several noncoding (nc)RNAs. It was found to associate with the microRNA let-7, 6,7 although the consequences of this interaction are unclear, and with several long noncoding (lnc)RNAs, including LINCRNAP21, HOTAIR, and RMRP, influencing their stability or subcellular localization. 6,8,9 However, whether or not HuR binds to circular RNAs (circRNAs) and the functional consequences of these interactions have not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past several years there have been reports of HuR's antagonistic as well as synergistic effect on miR function on a single mRNA (Meisner and Filipowicz 2011;Srikantan et al 2012). However, evidence from transcriptome-wide studies suggests that HuR antagonizes the destabilizing effect of miRs when bound at overlapping binding sites (Mukherjee et al 2011;Lu et al 2014). We found that HuR's binding sites residing within 10 nt of enriched miR target gene sets overlap predicted miR binding sites at frequencies greater than expected (Fig.…”
Section: Utility Of Whole-transcript Analysismentioning
confidence: 76%
“…5B). Given that HuR has been found to generally stabilize mRNA targets while AGO-miR binding is associated with decay of targeted mRNAs, it has been proposed that antagonism of AGO function by HuR may control the turnover of HuR mRNA targets (Mukherjee et al 2011;Lu et al 2014). These results support the conclusion that whole-transcript target analysis using DO-RIP-seq can reveal functionally related RNA targets and, together with binding site information, illuminate the importance of combinatorial relationships among RNA-binding proteins at the binding site level.…”
Section: Do-rip-seq Identifies Enriched Functional Gene Sets and Overmentioning
confidence: 99%
See 1 more Smart Citation
“…HuR is also implicated in gametogenesis, cell differentiation, and stem/progenitor cell survival (Levadoux-Martin et al 2003;Ghosh et al 2009). In macrophages, HuR is involved in the regulation of inflammatory and angiogenic processes (Zhang et al 2012;Lu et al 2014) HuR binds to mRNAs containing AU-rich element (ARE) and U-rich element (URE) (Abdelmohsen and Gorospe 2010). While these sequences are known to be destabilizing for the RNAs that contain them, the binding of HuR and HuD increases the stability of the target mRNAs and sometimes activates their translation (Jain et al 1997).…”
Section: Introductionmentioning
confidence: 99%